2021
DOI: 10.3892/etm.2021.11030
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality and COVID‑19: Suicidal ideation, suicidal behaviors and completed suicides amidst the COVID‑19 pandemic (Review)

Abstract: Since the outbreak of the coronavirus 2019 (COVID-19) pandemic, there has been widespread concern that social isolation, financial stress, depression, limited or variable access to health care services and other pandemic-related stressors may contribute to an increase in suicidal behaviors. In patients who have recovered from COVID-19, an increased risk of developing suicidal behaviors may be noted, while post-COVID syndrome comprises another potential risk factor contributing to increased suicidal behaviors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 86 publications
2
41
0
Order By: Relevance
“…Though mild symptoms predominated, moderate and severe depression were still more prevalent in infected patients than general society, in which the prevalence of moderate and severe depression is 5.1 percent and 1.5 percent, respectively. However, suicidality has not been shown to have necessarily increased during this pandemic, with a number of studies even finding instead an apparent decrease in the frequency of suicide attempts and self-harm [101].…”
Section: Depression Anxiety and Sleep Disordersmentioning
confidence: 99%
“…Though mild symptoms predominated, moderate and severe depression were still more prevalent in infected patients than general society, in which the prevalence of moderate and severe depression is 5.1 percent and 1.5 percent, respectively. However, suicidality has not been shown to have necessarily increased during this pandemic, with a number of studies even finding instead an apparent decrease in the frequency of suicide attempts and self-harm [101].…”
Section: Depression Anxiety and Sleep Disordersmentioning
confidence: 99%
“…As rates of depression have increased over the course of the pandemic (Ettman et al, 2022), one of the potential risks that might accompany that rise would be suicidal behaviour and ideation. At first glance, suicidality is a concept that is deceptively simple to conceptualize in the context of COVID-19, but is actually composed of multiple distinct facets including suicidal ideation (thoughts), suicide attempts, and completed suicides (Dubé et al, 2021;Efstathiou et al, 2022;Moutier, 2021). An international study conducted by Pirkis et al (2020) with over 20 countries examined suicide rates in the early months of the COVID-19 pandemic and found that there was no increase in suicide rates observed.…”
Section: Emerging Evidencementioning
confidence: 99%
“…Known risk factors for suicide in older individuals include depression ( 4 ), social isolation ( 5 ), alcoholism ( 6 ), retirement ( 7 ), and medical illness/physical disability ( 8 ). These risk factors have become even more important during the COVID-19 pandemic, which has disproportionately affected the elderly ( 9 , 10 ). New approaches to suicide research are attempting to develop integrated models that incorporate the myriad of complex neurobiological, psychological, and social factors that may contribute to suicidal behavior in both younger and older populations ( 11 ).…”
Section: Descriptionmentioning
confidence: 99%